In any ΔABC, prove that


In any ΔABC, prove that

$a(b \cos C-c \cos B)=\left(b^{2}-c^{2}\right)$



Left hand side,

$a(b \cos C-c \cos B)$

$=a b \cos C-a c \cos B$

$=a b \frac{a^{2}+b^{2}-c^{2}}{2 a b}-a c \frac{a^{2}+c^{2}-b^{2}}{2 a c}\left[A s, \cos C=\frac{a^{2}+b^{2}-c^{2}}{2 a b} \& \cos B=\frac{a^{2}+c^{2}-b^{2}}{2 a c}\right]$





$=$ Right hand side. [Proved]


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now